2013
DOI: 10.2147/ppa.s43465
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pill burden on dosing preferences, willingness to pay, and likely adherence among patients with type 2 diabetes

Abstract: PurposeTo quantify willingness-to-pay (WTP) for reducing pill burden and dosing frequency among patients with type 2 diabetes mellitus (T2DM), and to examine the effect of dosing frequency and pill burden on likely medication adherence.Patients and methodsParticipants were US adults with T2DM on oral antihyperglycemic therapy. Each patient completed an online discrete-choice experiment (DCE) with eight choice questions, each including a pair of hypothetical medication profiles. Each profile was defined by redu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 39 publications
2
38
0
1
Order By: Relevance
“…Similar outcomes have been documented in patients with HIV/AIDS who were on multiple antiretroviral medications and diabetics (Chesney, 2000;Hauber et al, 2013). The reasons that could be advanced for this include; the discomfort arising from the high 'pill burden' and the likelihood of more druginduced side effects due to multiple drug combinations.…”
Section: Discussionmentioning
confidence: 57%
“…Similar outcomes have been documented in patients with HIV/AIDS who were on multiple antiretroviral medications and diabetics (Chesney, 2000;Hauber et al, 2013). The reasons that could be advanced for this include; the discomfort arising from the high 'pill burden' and the likelihood of more druginduced side effects due to multiple drug combinations.…”
Section: Discussionmentioning
confidence: 57%
“…They found that lower frequency of administration, shorter administration times, and milder dry cough appeared to improve stated adherence to antibiotic treatment of CF lung infections. Hauber et al [21] examined patients' preferences for attributes of oral antihyperglycemic agents among patients with type 2 diabetes mellitus, and in the other study, the effect of pill burden on dosing preferences, willingness to pay, and likely adherence among the same group of patients [22]. In the first two studies the most important measures of effectiveness were glucose control, medication-related cardiovascular risk, and weight gain, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…In some disease states adherence is critical to survival rates, yet some degree of nonadherence is likely in a relatively high percentage of patients 54. Hauber et al found that patients are willing to pay for additional improvement not only in dosing frequency, but also in efficacy and side effects 55. In instances where long-term medical therapy is necessary to achieve desired outcomes, treatment efficacy can be compromised by suboptimal adherence, compliance, and persistence with the treatment in general.…”
Section: Bromfenac Compliance and Adherencementioning
confidence: 99%